Efektivitas Penggunaan Video Dalam Meningkatkan Motivasi Belajar Dan Prestasi Siswa Melalui Bimbingan dan Konseling Pada Siswa Kelas VIII SMPN 1 Tragah - Jumali, Jumali; Silver, Soesiana Tri Eka; Huda, Nuril (Jurnal Ilmiah Wahana Pendidikan, 2024)
The objectives of this research include: 1) To determine the effectiveness of using videos in increasing student learning motivation through guidance and counseling for class VIII students at SMPN 1 Tragah, and 2) To determine the effectiveness of using videos in increasing student achievement through guidance and counseling for class students. viii SMPN 1 Tragah. Researchers conducted trials on the use of videos in providing guidance and counseling services to increase student motivation and achievement. These researchers are included in the type of experimental research. Experimental research is research that uses a quantitative research approach where data is produced in the form of numbers and analyzed using statistical analysis techniques. Nonequivalent Control Group Design is the experimental research design chosen and is one of the quasi experimental design research designs. The research samples were 30 students from class VIII-C as the control class and 30 students from class VIII-D as the experimental class. Researchers developed an instrument in the form of a questionnaire on learning motivation and career planning. The data obtained were analyzed using the independent sample t test analysis technique. Research conclusions include: 1) The use of videos is effective in increasing student learning motivation through guidance and counseling for class VIII students at SMPN 1 Tragah., 2) The use of videos is effective in improving student achievement through guidance and counseling for class VIII students at SMPN 1 Tragah.